Madrid DF. - González Garcia, Angel (Madrid : Museo Municipal, 1980)
Aguirre, Juan Antonio ; Albacete, Alfonso ; Alcolea, Carlos ; Campano, Miguel Angel ; Lootz, Eva ; Navarro Baldeweg, Juan ; Ortuño, Pancho ; Pérez Villalta, Guillermo ; Quejido, Enrique ; Quejido, Manolo ; Schlosser, Adolfo ; Serrano, Santiago
Madrid DF, Museo Municipal, Madrid, Octubre - Noviembre 1980
boek
Keywords: Madrid